Thicker than water ebook A novel. - Collins, Megan (2023)
In this "twisty, propulsive thriller" (Robyn Harding, internationally bestselling author) from Megan Collins, two sisters-in-law are at painful odds when the man who connects them—the brother of one, the husband of the other—is accused of a brutal crime. Julia and Sienna Larkin are sisters-in-law, connected by Julia's husband and Sienna's brother, Jason. More than that, the two are devoted best friends and business partners, believing that theirs is a uniquely unbreakable bond. To Sienna, her protective brother can do no wrong, and although Julia knows he's not perfect, they've built a comfortable life and family together. Recently, Jason has been putting in long hours to secure a promotion at work, so when his boss is found brutally murdered—his lips sewn shut—the Larkins are shocked and unsettled, especially as local gossip swirls. A few days later, Julia and Sienna's lives are upended when Jason gets into a car accident and is placed in a medically induced coma. Worse, the police arrive with news that he's the prime suspect in the murder investigation. With Jason unable to respond—and with Julia and Sienna working to clear his name—the two women find their friendship threatened for the first time: Sienna staunchly maintains her brother's innocence, but as their investigation uncovers a complicated web of secrets, Julia is less sure she's willing to defend her husband. With her signature "moody and atmospheric" ( USA TODAY ) writing, Megan Collins has crafted a rich, gripping story that explores just how fragile our closest bonds can be.